Personen v.l.n.r.: Bax, Van Kol, Kleerekoper (inzet), Van der Kieft en Troelstra. Tekst onder tekening - Roode-Heijermans, Marie de,
Personen v.l.n.r.: Bax, Van Kol, Kleerekoper (inzet), Van der Kieft en Troelstra. Tekst onder tekening.